Lexical Equivalence of Bugis–Indonesian–English Vocabulary in Bilingual Dictionaries and Its Implications for English Language Teaching - Ibnu Quraish (Sumber Belajar Sejahtera, 2026)
This study investigates the translation strategies applied to Bugis vocabulary in Douglas Laskowske’s Bugis–Indonesian–English Dictionary, focusing on the use of literal translation and dynamic equivalence. Out of 239 lexical entries analyzed, 148 were translated literally (62%) and 91 through dynamic equivalence (38%). Literal translation proved effective for general vocabulary with clear equivalents, while dynamic equivalence was essential for culturally embedded terms, ceremonies, and social concepts. Interviews with native speakers revealed that literal translations often fail to capture deeper cultural meanings, whereas dynamic strategies preserve symbolic, emotional, and contextual nuances. Teacher interviews further emphasized that learners benefit most when cultural notes, paraphrasing, and critical dictionary use are integrated into English Language Teaching (ELT). The findings validate Eugene Nida’s theory of equivalence, highlighting the translator’s role as a cultural mediator and demonstrating that bilingual dictionaries function not only as linguistic tools but also as cultural bridges. This research contributes to translation studies and language pedagogy by showing that culturally sensitive translation enhances vocabulary learning, fosters intercultural competence, and supports the preservation of Bugis cultural heritage.